Relative Abundance of Ceratitis capitata and Anastrepha fraterculus (Diptera: Tephritidae) in Diverse Host Species and Localities of Argentina - Segura, Diego Fernando (2006)
Two fruit fly species (Diptera: Tephritidae) of economic importance occur in Argentina, the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), and Anastrepha fraterculus (Wiedemann). Here, we compared the relative abundance of these fruit pests in 26 fruit species sampled from 62 localities of Argentina in regions where C. capitata and A. fraterculus coexist. In general, C. capitata was predominant over A. fraterculus (97.46% of the emerged adults were C. capitata), but not always. Using the number of emerged adults of each species, we calculated a relative abundance index (RAI) for each host in each locality. RAI is the abundance of C. capitata relative to the combined abundance of A. fraterculus and C. capitata. Some families of fruit species were more prone to show high (Rutaceae and Rosaceae) or low (Myrtaceae) RAI values, and also native plants showed lower RAI values than introduced plants. RAI showed high variation among host species in different localities, suggesting a differential use of these hosts by the two flies. There were localities where A. fraterculus was not found in spite of suitable temperature and the presence of hosts. Most host species showed little variation in RAI among localities, usually favoring C. capitata, but peach, grapefruit, and guava showed high variation. This suggests that these fruit species are suitable for both fruit flies but more favorable to one or the other, depending on local environmental conditions (e.g., relative humidity and degree of disturbance) of each locality.